The Role of Accounting in Supporting Marketing Strategy at PT Sari Alam Sukabumi - Putri, Anisa; Dania Meida Rosyidah (Edumedia Solution, 2026)
This community engagement program was carried out to address several challenges faced by PT Sari Alam Sukabumi, particularly the suboptimal use of accounting data and the limited effectiveness of the company’s marketing strategies. Although the company manages more than 400 extract products, the existing financial and sales data had not been systematically utilized to support decision-making in pricing, promotional planning, and customer targeting. The implementation methods consisted of field observation, data collection, analysis of sales and financial records, development of a structured product database, preparation of margin-based price lists, and assistance in designing digital promotional materials and broadcast communication strategies. Throughout the activity, the product database was reorganized, sales performance graphs were produced, and a comprehensive price list was developed to aid in marketing negotiations. Digital promotional efforts through email and WhatsApp broadcasts also helped expand the company’s market reach. The outcomes indicate significant improvements in data organization, pricing accuracy, and marketing effectiveness. Overall, the program successfully addressed the partner’s core problems by integrating accounting analysis into marketing practices and strengthening the company’s capacity for data-driven decision-making.